Elaboration and characterization of PVP-assisted NiO thin films for enhanced sensitivity toward H2 and NO2 gases. Issue 5 (1st April 2019) - Zargouni, S.; Derbali, L.; Ouadhour, M.; Rigon, M.; Martucci, A.; Ezzaouia, H.
Abstract: It is widely demonstrated that the synthesis conditions of sol-gel films have a great impact on their gas sensing properties. In this work, transparent PVP-assisted nickel oxide thin films with an average grain size of ~5 nm were synthesized using two distinctive deposition procedures combining the sol-gel method with the spin-coating technique then tested as optical gas sensors for the detection of hazardous pollutant gases. The first method is ascribed to a typical spin-coating deposition followed by a thermal annealing, and the second method consisted on a multistep coating annealing process. Structural and morphological studies showed enhanced crystallization rate and homogeneous surface morphology using a multistep deposition. The as prepared films exhibit a clear and reversible response toward H2, CO and NO2 gases and the multistep deposition process enhanced the sensitivity of about 113% and 194% toward 1% of H2 and 0.1% of NO2 respectively. The shrinkage of the band gap from 4.07 to 3.91 eV and the increased PL intensity indicate the presence of higher rate of charge density and intrinsic defect states that promoted the sensitivity of the film. Furthermore, improved response intensity was detected in the near UV region and higher stability with fast response was obtained for hydrogen gas.